PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi empiris pada perusahaan property dan real estate yang terdaftar di BEI tahun 2013-2015) - Benni Sumardi; Kamaliah Kamaliah; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the influence of firm characteristics on corporate social responsibility disclosure. This study was conducted on property and real estate companies listed on the Indonesia Stock Exchange. Data collection techniques in this study form of data collection method documentary. The number of samples in this study are as many as 90 companies. While the method of analysis used in this study is multiple linear regression analysis with the help of SPSS version 20 program. The results showed that the size of the board of commissioners, profitability, age of company, and company size affect the disclosure of corporate social responsibility, while Leverage does not affect the disclosure of corporate social responsibility. The coefficient of determination by the four variables in this study affect the dependent variable by 41%, while 59% is influenced by other variables not described in this study.Keywords : Size of board of commissioners, Profitability, Leverage, Age of company, Company size and corporate social responsibility disclosure